Politicians and Economic Experts The Limits of Technocracy. - Killick, Anna (Agenda Publishing, 2022)
In recent years politics has seen an increasing role in economic policy-making for a technocracy of experts. How do politicians feel about this and how do they balance their political and ethical aims with economic expertise?